2014
DOI: 10.1159/000365001
|View full text |Cite
|
Sign up to set email alerts
|

A Report of Disseminated Carcinomatosis of the Bone Marrow Originating from Transverse Colon Cancer Successfully Treated with Chemotherapy Using XELOX plus Bevacizumab

Abstract: A 61-year-old male, who had been admitted to another hospital due to disseminated intravascular coagulation (DIC), was referred to our hospital. Total colonoscopy, abdominal dynamic CT and positron-emission tomography revealed bone metastasis and multiple lymphocytic metastases from transverse colon cancer in addition to disseminated carcinomatosis of the bone marrow (DCBM). We immediately performed chemotherapy with XELOX + bevacizumab and denosumab against DCBM from transverse colon cancer in order to avoid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 25 publications
(25 reference statements)
0
16
0
Order By: Relevance
“…In that study, 37 of the 40 cases (92.5%) were due to gastric cancer while one each was due to prostate, gallbladder, and ovarian cancer with unknown primary lesion, but no case of colorectal cancer was reported. A review of the literature revealed that DCBM in colorectal cancer is particularly rare and only 10 cases have been reported previously (Table 1) [8][9][10][11][12][13][14][15][16][17]. The average age of the patients was 61.0 years (men, 9 cases; women, 2 cases).…”
Section: Discussionmentioning
confidence: 99%
“…In that study, 37 of the 40 cases (92.5%) were due to gastric cancer while one each was due to prostate, gallbladder, and ovarian cancer with unknown primary lesion, but no case of colorectal cancer was reported. A review of the literature revealed that DCBM in colorectal cancer is particularly rare and only 10 cases have been reported previously (Table 1) [8][9][10][11][12][13][14][15][16][17]. The average age of the patients was 61.0 years (men, 9 cases; women, 2 cases).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been hypothesized that IL-3, IL-5 and other cytokines are involved in the differentiation and maturation of eosinophils (1,5,13,14). An association between bone marrow carcinogenesis and eosinophilia has been suggested (15), and although it is rare, previous studies have reported cases of bone marrow carcinogenesis accompanied by colon cancer (15,16). The patient in the present case underwent a blood transfusion to control bleeding caused by tumor hemorrhage and DIC, and then underwent emergency surgery; therefore, it was not possible to measure cytokine levels or perform bone marrow tests prior to surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In the contrary, colorectal cancer remains a rare cause of DCBM, with rectal cancer slightly more frequent. In one study, only 27 cases of colorectal cancer are reported, as an origin of DCBM, between 1984 and 2013 in Japan [1].…”
Section: Discussionmentioning
confidence: 99%
“…Various chemotherapy regimens are used for this purpose with different outcomes [4][5][6][7][8][9][10][11][12]. Although survival is improved in most cases, patients with colorectal cancer and DCBM do not survive more than 100 days [1]. Yoshida et al [13] report the early start of chemotherapy after surgery in patients with colorectal cancer and synchronous metastases, aiming at preventing tumor growth.…”
Section: Discussionmentioning
confidence: 99%